Konsep Keadilan bagi Nasabah dalam Penerapan Akad Murabahah bil Wakalah di Bank Syari'ah - Ifghania, Farras Yola Else (UPT Publikasi Ilmiah UNISBA, 2019)
The principle of wakalah is applied in murabahah financing products, namely murabahah bil wakalah. The bank acts as a representative in buying goods and the bank submits money to customers to become a representative. For the customer's work, there is even injustice between the Islamic bank and the customer. As happened in the product of service in general, banks as parties that are given the mandate to get fees from customers. However, in the practice of murabahah financing, customers who become representatives do not receive fees from the bank as muwakkil. The formula for this research is (1) How is the application of the murabahah bil wakalah contract to Islamic banks? and (2) What is the justice for customers in the murabahah bil wakalah contract for Islamic banks? The method used is a qualitative research method. The type of research used in this study is library research, which is a form of methodology for collecting data and information with the help of books in the library, and other library materials. The results of this study are in practice the purchase of murabahah objects can be done by the customer as a representative of the bank with a wakalah contract. The customer acts for and on behalf of the Islamic bank to purchase the murabahah object. After the wakalah contract is completed, the murabahah object in principle has become the property of the Islamic bank so that the next contract can be carried out, namely the murabahah contract. Judging in the murabahah bil wakalah contract the value of justice is still not evenly distributed, so that from the relationship between the customer and the bank, the bank benefits more.